Bank performance : a theoretical and empirical framework for the analysis of profitability, competition and efficiency - Bikker, Jacob A., 1952-; Bos, Jaap W. B. (London ; New York : Routledge, 2008)
This book provides an all-embracing framework for the various existing theories in this area and illustrates these theories with practical applications. Evaluating a broad field of research, the book describes a profit maximizing bank and demonstrates how several widely-used models can be fitted into this framework. The authors also present an overview of the current major trends in banking and relate them to the assumptions of each model, thereby shedding light on the relevance, timeliness and shelf life of the various models. The results include a set of recommendations for a future research agenda. Offering a comprehensive analysis of bank performance, this book is useful for all of those undertaking research, or are interested, in areas such as banking, competition, supervision, monetary policy and financial stability.
Includes bibliographical references (p. [143]-150) and index.
rpm 09/05/13
Loans
Keywords: Bank management; Banks and banking